Examining the Relocation of the Capital City of Indonesia Through the State Perspective in Political Economy - Ana Sabhana Azmy (Polit Journal Scientific Journal of Politics, 2021)
The government's decision to move the capital of the Republic of Indonesia from DKI Jakarta to Kalimantan has drawn pros and cons among the public. The government considers the relocation plan to provide comfort, welfare, access to education, health and fair and equitable participation. However, moving the capital city is not easy and must go through a well-planned plan. Using a literature study, this article attempts to review how the state positions itself in the relocation plan, and what are the implications for relocating the capital city in the context of economic development. The conclusion of this discourse is that the state is exercising its autonomy in the plan to move the capital city, or what Caporaso and Levine say as a free state. The government remains focused on relocation plans, although there are a number of people who disagree. The government also ensures that the implications of the capital relocation plan are positive for economic development in Indonesia. distribution of economic equality will occur in Indonesia.